Remarks on practice. participatory construction of communication guidelines in NGOs - Mejía Vásquez, Doris (2008)
This paper describes the process followed by an internarional NFO, ITDG -Practical Solutions, to improve communication impact on its practices and institutional policies. It shows an inventory of the main challenges that NGOs are facing in the field of communication, the inrernarional scenario factors which generate them and the route this organization followed to meet them. The designed program, advances and lessons learned in the way, and also the considerations that must be taken to follow similar processes are described in detail.